Relationship of anxiety with emotional and behavioral problem in Madrasah Tsanawiyah Hidayatullah Islamic boarding school students, Denpasar - Rabiatul Udawiyah; Cokorda Bagus Jaya Lesmana; Lely Setyawati (Journal of Clinical and Cultural Psychiatry, 2020)
Background: Emotional and behavioral problem are persistent and recurring problem that observed in teenagers specifically students. Anxiety is the most common mental health problem found in Islamic boarding school students. This research aims to find out the relationship of anxiety with emotional and behavioral problem in Madrasah Tsanawiyah, Hidayatullah Islamic Boarding School Students, Denpasar. Patients and Methods: The study was an analytical cross-sectional study with 89 students met inclusion and exclusion criteria. This research used the Strength and Difficulties Questionnaire (SDQ) to measure emotional and behavioral problems and Beck Anxiety Inventory (BAI) to measure the student’s anxiety level. The correlation was analyzed by using Spearman’s correlation test. Results: Forty-five (50.8%) students experience abnormal emotional and behavioral problems with 30 (30%) the students mostly had moderate level anxiety. The correlation between the anxiety with emotional and behavioral problems had an R value of 0.366 (p<0.001). Conclusion: There was a moderate positive relationship between anxiety with emotional and behavioral problems in Madrasah Tsanawiyah Islamic boarding school Hidayatullah students.